Innovation in Utilizing Plastic Waste into Ecobrick Pots at SD Negeri Keleyan 1 Socah Bangkalano Ecobrick Pots at SD Negeri Keleyan 1 Socah Bangkalan - Nugroho, Hendra Herlambang; Amrosi, Achmad; Maulidina, Annisa Putri Azalia; Fadlillah, M. (Society : Jurnal Pengabdian Masyarakat, 2026)
Plastic waste is one of the major environmental problems that continues to increase, including within school environments. Its non-biodegradable nature makes plastic a type of waste that potentially pollutes soil, water, and air if not properly managed. This study aims to evaluate the effectiveness of an ecobrick pot-making program in reducing the amount of plastic waste at SD Negeri Keleyan 1 Socah Bangkalan, to raise students’ and teachers’ awareness of sustainable waste management, and to assess the use of ecobricks as planting media. This research employed a qualitative approach with an Action Research method carried out through the stages of planning, action, observation, and reflection. Data collection techniques included observation, interviews, and documentation. The results showed that the ecobrick program successfully reduced the amount of scattered plastic waste, prevented waste-burning practices, and transformed plastic into useful planting pots. In addition, the program enhanced the participation of students, teachers, and parents in maintaining school cleanliness and fostered collective awareness of environmentally friendly behavior. In conclusion, the ecobrick program at SD Negeri Keleyan 1 Socah Bangkalan proved effective in reducing plastic waste accumulation while simultaneously supporting school greening activities through the utilization of ecobricks as planting media.